2013
DOI: 10.1093/eurjhf/hfs216
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate recovery after the 6 min walk test rather than distance ambulated is a powerful prognostic indicator in heart failure with reduced and preserved ejection fraction: a comparison with cardiopulmonary exercise testing

Abstract: Aims Heart rate recovery (HRR) appears to be a robust prognostic marker in heart failure (HF). When using the 6 min walk test (6MWT) in HF, distance ambulated is generally the reference prognostic variable. We hypothesized that HRR after the 6MWT would be a better prognostic measure than distance ambulated. Methods and results A 6MWT and cardiopulmonary exercise testing (CPX) were randomly performed in 258 HF patients [216 HF with reduced EF (HFrEF) and 42 HF preserved EF (HFpEF)], after which HRR was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 29 publications
5
49
1
3
Order By: Relevance
“…A few others studied the value of CPX in patients with HFpEF. [20][21][22] Guazzi et al compared CPX parameters with multiple variables between an HFrEF and an HFpEF population. 20 Although that study showed that the VE/VCO2 slope represents HFpEF severity, no relationship between the VE/VCO2 slope and mortality was studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few others studied the value of CPX in patients with HFpEF. [20][21][22] Guazzi et al compared CPX parameters with multiple variables between an HFrEF and an HFpEF population. 20 Although that study showed that the VE/VCO2 slope represents HFpEF severity, no relationship between the VE/VCO2 slope and mortality was studied.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that in the combined population with predominantly HFrEF patients, the VE/VCO2 slope was a significant prognostic parameter in the 6-minute walk test, and they found that the VE/VCO2 slope was the only predictor of major cardiac events. 21 Nedeljkovic et al studied the value of CPX as a diagnostic tool for HFpEF. They concluded that the VE/ VCO2 slope could be a reliable test to diagnose HFpEF in an early stage, but they did not investigate the possible association between VE/VCO2 and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, HRR 1 after the 6MWT in COPD as a prognostic factor has never been reported. This is a tangible clinical finding given that the 6MWT is a widely used, simple test to apply into the clinical scenario (12).…”
Section: Discusionmentioning
confidence: 99%
“…20 The other determinant of Fick principle is O 2 extraction, a biological phenomenon related to O 2 delivery and diffusion from capillaries to mitochondria. When O 2 is adequately dispatched by cardiac output, its extraction depends on the amount of blood flow redistribution to vascular beds of exercising muscles and several molecular facilitating mechanisms, including PO 2 , the Hb concentration and the pressure of O 2 corresponding to the 50% of Hb half saturation with O 2 (P 50 ).…”
Section: Article See P 33mentioning
confidence: 99%